2017
DOI: 10.2147/ceg.s130449
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic esophageal myotomy versus pneumatic dilation in the treatment of idiopathic achalasia: a meta-analysis of randomized controlled trials

Abstract: BackgroundAchalasia is a primary esophageal motility disorder of unknown etiology associated with abnormalities in peristalsis and lower esophageal sphincter relaxation. The disease is incurable; however, definitive treatment procedures like pneumatic dilation (PD)/balloon dilation and laparoscopic esophageal myotomy (LEM) are performed to relieve dysphagia and related symptoms. Currently, there is paucity of data comparing the outcomes of these procedures. The aim of this meta-analysis is to compare the short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
5
1
Order By: Relevance
“…In this study, the mortality rate 30 days after PD was surprisingly high with a staggering 1.9% 1. This is contradictory to previous recent literature, in which the mortality rate after pneumatic dilatation was generally 0% 2–4. In the current study, subjects were excluded if they had a prior diagnosis of achalasia in the preceding 5 years since the introduction of ICD-10 coding in 2001.…”
contrasting
confidence: 73%
See 1 more Smart Citation
“…In this study, the mortality rate 30 days after PD was surprisingly high with a staggering 1.9% 1. This is contradictory to previous recent literature, in which the mortality rate after pneumatic dilatation was generally 0% 2–4. In the current study, subjects were excluded if they had a prior diagnosis of achalasia in the preceding 5 years since the introduction of ICD-10 coding in 2001.…”
contrasting
confidence: 73%
“…The perforation rate (1.6%) was at the lower end of the range provided by the literature (0%–5%), which seems unexpected given the high mortality found 2 3. The authors state that under-reporting of complications is possible in HES data, which could explain the lower perforation rate.…”
mentioning
confidence: 66%
“…The results of a meta-analysis including 361 patients showed that LHM may provide greater response rates than graded endoscopic PBD in the treatment of newly diagnosed idiopathic achalasia (5). Two recent meta-analysis comparing the outcomes of endoscopic PBD and LHM revealed similar results at 5-year intervals (16,17). An evidence-based approach study, which searched PubMed/ Medline electronic databases and the Cochrane Library, stated that LHM+partial fundoplication was associated with lower complication rates and provided excellent long-term results with lower need for the additional treatment of recurrent dysphagia than endoscopic PBD (18).…”
Section: Discussionmentioning
confidence: 99%
“…Besides BD, other therapeutic possibilities are developing [27][28][29][30][31][32] but this method will remain the most convenient option for most patients.…”
Section: Discussionmentioning
confidence: 99%